W. V. Quine'ın Analitiklik Eleştirisi - (:unkn) unknown (My University, 2007)
0

This study deals with W. V. Quine's critique of analyticity he developed in his article entitled "Two Dogmas of Empiricism". In it, Quine rejects outright the analytic/synthetic distinction. In the history of philosophy, after Kant as distinction of analytic and synthetic systematically, it was Carnap who firstly exposed the division of statements as analytic and synthetic in a logically sense. What Carnap actually did was to fint out the notion of analyticity on logical basis through his syntax theory. That is why, Quine argues directly against Carnap. Quine argues that analyticity cannot be explicated semantically without falling into a circularity. Therefore, Quine, examines the notion of synonymy, meaning, definition, interchangeability and semantical rules and shows that one way or another all these notions presuppose the nation of analyticity. In this article, it is claimed that Quine's criticisms against Carnap are methodologically irrelesant. They make sense only in an epistemological context.
W. V. Quine's Critique of Analyticity
Keywords: Felsefe